2006
DOI: 10.4319/lom.2006.4.216
|View full text |Cite
|
Sign up to set email alerts
|

A new automated setup for stable isotope analysis of dissolved organic carbon

Abstract: The measurement of stable isotope ratios on dissolved organic carbon (DOC) has long posed analytical problems and limited the use of this powerful tracer in biogeochemical studies in aquatic systems. Here, we provide a detailed description of a successful coupling of a custom-modified total organic carbon analyzer (Thermo HiPerTOC) to an isotope-ratio mass spectrometer (IRMS). The method is based on the wet oxidation of up tõ 20 mL aqueous sample in a closed reactor, whereby complete oxidation is ensured by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 27 publications
4
57
0
Order By: Relevance
“…4c). Differences in the origin of particulate and dissolved organic carbon have previously been documented (Bouillon et al, 2006), but rarely as pronounced as shown here. More importantly, our study provides clear mechanisms explaining these strong variations (summarized in Sect.…”
Section: Origin and Exchange Of Organic Mattermentioning
confidence: 67%
See 1 more Smart Citation
“…4c). Differences in the origin of particulate and dissolved organic carbon have previously been documented (Bouillon et al, 2006), but rarely as pronounced as shown here. More importantly, our study provides clear mechanisms explaining these strong variations (summarized in Sect.…”
Section: Origin and Exchange Of Organic Mattermentioning
confidence: 67%
“…Samples for DOC and δ 13 C DOC were obtained by pre-filtering surface water on pre-combusted Whatman GF/F filters, followed by filtration on 0.2 µm cellulose acetate syringe filters (Sartorius), and preserved by addition of 50 µL of H 3 PO 4 . DOC concentrations and δ 13 C signatures were measured with a modified Thermo HiperTOC TOC-analyzer, interfaced with a Thermo delta +XL IRMS as described by Bouillon et al (2006).…”
Section: Methodsmentioning
confidence: 99%
“…DOC was analysed according either on a Thermo HiperTOC-isotope ratio mass spectrometer (IRMS) or with an Aurora1030 TOC analyser (OI Analytical) coupled to a Delta V Advantage IRMS, with a precision better than ±5% (ref. 35) (refs 37,38). The detection limits were 0.30 and 0.15 µmol l −1 for NH 4 + and NO 3 − , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, estuaries and proximal continental shelves typically sustain high biological productivity (Walsh et al, 1981;Wollast, 1993Wollast, , 1998Cai, 2003), which may draw down CO 2 . This phenomenon, however, may be more than counteracted by enhanced heterotrophic activity, supported by organic carbon input from rivers (Smith and Hollibaugh, 1993;Heip et al, 1995;Hedges and Keil, 1995;Hedges et al, 1997;Hansell and Carlson, 1998;Bouillon et al, 2006;Jiang et al, 2010). Additionally, direct inorganic carbon input from river water, submarine groundwater discharge and exchanges with tidal marshes and mangroves play an important role in increasing the pCO 2 of estuarine and shelf waters (Moran et al, 1991;Miller and Moran, 1997;Neal et al, 1998;Raymond and Bauer, 2001;Borges et al, , 2006Cai et al, 2003;Wang and Cai, 2004;Jahnke et al, 2005;Bouillon et al, 2008;Jiang et al, 2008aJiang et al, , 2010Chen et al, 2012).…”
Section: C-t a Chen Et Al: Air-sea Exchanges Of Co 2 In The Worldmentioning
confidence: 99%